Numerical analysis of a fin-tube plate heat exchanger with winglets - Muhsin Al-Juhaishi, Lafta Flayih (2014)
In this presented work, numerical analysis of heat transfer and flow characteristic using longitudinal vortex generators (LVGS) in fin and flat tube heat exchanger has been presented. Conjugate heat transfer 3D numerical model has been developed and successfully carried out. Rectangular winglets were set in pairs, with downstream orientation. The effects of impact angles of (20⁰ , 30⁰, and 40⁰ ) as well as tubes and winglets were placed in one row lined arrangement and air flow by forward arrangement and backward arrangement. Reynolds number is ranged from 500 to 5000. The numerical results showed that in the range of the present study, the variation of these parameters can result in the increase of heat transfer. The study focuses on the Influence of the different parameters of VGs on heat transfer and fluid flow characteristics of one row lined circular-tube banks. The characteristics of average Nu number and skin friction coefficient are studied numerically by the aid of the computational fluid dynamics (CFD) commercial code of FLUENT ANSYS 14. The results showed increasing in the heat transfer and skin friction coefficient with the increasing of Re number. It has been observed that the overall Nuav number of one circular tubes increases by 23-31% ,by 23-43% and by 23-47% with angles of (20⁰, 30°, and 40⁰) respectively, in forward arrangement and the overall Nuav number of one circular tubes increases by 23-42%, by 23-46% and 23-52%with angles of (20⁰, 30°, and 40⁰) respectively, in backward arrangement, with increasing in the overall average of skin friction coefficient. Also the results showed that the rectangular winglet pairs (RWPs) can significantly improve the heat transfer performance of the fin and-tube heat exchangers with a moderate pressure loss penalty.